ANALISIS DAMPAK PENGGUNAAN GAME ONLINE TERHADAP MINAT BELAJAR SISWA SMP DAERAH HU’U DOMPU - Amin, M.; Riski, Fathul (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
Online games can be interpreted as a program that displays visuals, animations and images that can move or be moved manually. Online games can be played with devices such as smartphones which can be played when a device is connected to an internet network. This study aims to determine the impact of using online games on students' interest in learning class VIII A at SMP Negeri Hu'u. This type of research is qualitative with a case study approach. The collection of data used in research observation, interviews and documentation. The participants used in the study included students who played online games, homeroom teachers, and parents of students who played online games. The results of the study showed that there was an influence on the impact of using online games on the learning interest of class VIIIA students of Junior High School. That students at SMP Negeri Hu'u usually play online games at school, they play in front of the classroom and in the school canteen and after school sometimes until the afternoon and continue into the evening. On average, students play online games Free Fire and Mobile Legend. Because of the preoccupation of playing online games, sometimes they will also forget to do their assignments and obligations, both helping their parents and doing their schoolwork, and students who are addicted to online games, they are also less enthusiastic about taking lessons after they play games because they are concerned about the game so that it reduces their interest in learning.